The ‘grave disease’: interwar British writers look at ragtime and jazz - Lawson-Peebles, Robert (Jazz Research Journal, 2014)
This essay is about the reaction of a group of interwar British writers to American popular music, to which (in the absence of more precise definitions) they give the terms ragtime and jazz. The group, mostly still well-known, includes John Buchan, Aldous Huxley, Eric Linklater, J. B. Priestley and Aelfrida Tillyard. Despite greatly differing political, social, racial and biological agendas, these writers depicted ragtime and jazz as symptoms of a mass produced, corrupt, sex-ridden culture that was contaminating an ageing European culture, fatally weakened by the First World War. The writers use language borrowed from pathology to suggest that such music attacks the moral as well as the physical constitution.